Validation of administrative hospital data for identifying incident pancreatic and periampullary cancer cases: a population-based study using linked cancer registry and administrative hospital data in New South Wales, Australia. Issue 7 (1st July 2016) - Creighton, Nicola; Walton, Richard; Roder, David; Aranda, Sanchia; Currow, David
Abstract : Objectives: Informing cancer service delivery with timely and accurate data is essential to cancer control activities and health system monitoring. This study aimed to assess the validity of ascertaining incident cases and resection use for pancreatic and periampullary cancers from linked administrative hospital data, compared with data from a cancer registry (the 'gold standard'). Design, setting and participants: Analysis of linked statutory population-based cancer registry data and administrative hospital data for adults (aged ≥18 years) with a pancreatic or periampullary cancer case diagnosed during 2005–2009 or a hospital admission for these cancers between 2005 and 2013 in New South Wales, Australia. Methods: The sensitivity and positive predictive value (PPV) of pancreatic and periampullary cancer case ascertainment from hospital admission data were calculated for the 2005–2009 period through comparison with registry data. We examined the effect of the look-back period to distinguish incident cancer cases from prevalent cancer cases from hospital admission data using 2009 and 2013 as index years. Results: Sensitivity of case ascertainment from the hospital data was 87.5% (4322/4939), with higher sensitivity when the cancer was resected (97.9%, 715/730) and for pancreatic cancers (88.6%, 3733/4211). Sensitivity was lower in regional (83.3%) and remote (85.7%) areas, particularly in areas with interstate outflow of patients for treatment, and for cases notified to the registry by death certificate only (9.6%). The PPV for the identification of incident cases was 82.0% (4322/5272). A 2-year look-back period distinguished the majority (98%) of incident cases from prevalent cases in linked hospital data. Conclusions: Pancreatic and periampullary cancer cases and resection use can be ascertained from linked hospital admission data with sufficient validity for informing aspects of health service delivery and system-level monitoring. Limited tumour clinical information and variation in case ascertainment across population subgroups are limitations of hospital-derived cancer incidence data when compared with population cancer registries.